Starter feed for carnivorous species as a practical replacement of bloodworms for a vertebrate model organism in ageing, the turquoise killifish Nothobranchius furzeri - Žák, Jakub; Roy, Koushik; Dyková, Iva; Mráz, Jan; Reichard, Martin (Journal of fish biology, 2022)
The absence of a controlled diet is unfortunate in a promising model organism for ageing, the turquoise killifish (Nothobranchius furzeri Jubb, 1971). Currently captive N. furzeri are fed bloodworms but it is not known whether this is an optimal diet. Replacing bloodworms with a practical dry feed would reduce diet variability. In the present study, we estimated the nutritional value of the diet ingested by wild fish and determined the fish-body amino acid profile as a proxy for their nutritional requirements. We compared the performance of fish fed four commercial feeds containing 46%-64% protein to that achieved with bloodworms and that of wild fish. Wild fish target a high-protein (60%) diet and this is supported by their superior performance on high-protein diets in captivity. In contrast, feeds for omnivores led to slower growth, lower fecundity and unnatural liver size. In comparison to wild fish, a bloodworm diet led to lower body condition, overfeeding and male liver enlargement. Out of the four dry feeds tested, the fish fed Aller matched wild fish in body condition and liver size, and was comparable to bloodworms in terms of growth and fecundity. A starter feed for carnivorous species appears to be a practical replacement for bloodworms for N. furzeri. The use of dry feeds improved performance in comparison to bloodworms and thus may contribute to reducing response variability and improving research reproducibility in N. furzeri research.
Keywords: Fundulidae; Carnivory; African killifish; stárnutí; mužské pohlaví; Aging; Reproducibility of Results; nutritional ecology; zvířata; practical diet; reprodukovatelnost výsledků; Cyprinodontiformes; laboratory diet; masožravci; Male; Animals